Apache Kafka series : Kafka streams for data processing - Maarek, Stéphane (Packt Publishing, 2018)
"The new volume in the Apache Kafka Series! Learn the Kafka Streams data-processing library, for Apache Kafka. Join hundreds of knowledge savvy students in learning one of the most promising data-processing libraries on Apache Kafka. This course is based on Java 8, and will include one example in Scala. Kafka Streams is Java-based and therefore is not suited for any other programming language. This course is the first and only available Kafka Streams course on the web. Get it now to become a Kafka expert!"--Resource description page